Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem-Based Learning Berbantuan Canva di Sekolah Dasar - Kurnia Wahyu Saputri; Desyandri Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
This research is motivated by the low learning outcomes of students in integrated thematic learning. The purpose of this study is to describe the increase in student learning outcomes in integrated thematic learning using the Canva-assisted Problem-Based Learning Model in class III elementary school. Data collection techniques used to obtain valid data in this study were: Analysis Documents, Observations, Tests and Non-Tests. The data collection instruments used in conducting this classroom action research were in the form of Lesson Plan Assessment Sheets, Observation sheets of teacher activities, and student activities. And the Evaluation Question sheet and the Skills Assessment Rubik. The results of the study showed an increase, in the lesson plans for the cycle I obtained an average of 82% and cycle II to 94%. Aspects of the cycle I teachers get an average of 83% and cycle II to 93%. The aspect of students in cycle I obtained an average of 83% and in cycle II it became 93%. Student learning outcomes in cycle I obtained an average of 77% and in cycle II it increased to 93%. Thus it can be concluded that the Canva-assisted Problem-Based Learning model can improve student learning outcomes in integrated thematic learning.